1984
DOI: 10.3109/00207458408985353
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Monosodium Glutamate (MSG) Treatment Given Through the Mother's Diet Causes Behavioral Deficits in Rat Offspring

Abstract: The present study reports various developmental and behavioral changes in the offspring of rat dams that received monosodium glutamate (MSG) in the drinking water all through the second and third trimesters of pregnancy. Three main effects were observed in the MSG exposed offspring: (1) juvenile obesity; (2) reduced general activity levels; (3) a specific type of learning disability in discrimination learning involving choice between simultaneously present positive and negative stimuli.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
1

Year Published

1988
1988
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 17 publications
2
24
0
1
Order By: Relevance
“…MSG was shown to penetrate the placental barrier and to distribute to embryonic tissues (Frieder and Grimm, 1984;Yu et al, 1997). The results of the present work revealed that oral administration of MSG to the pregnant and lactating mother rats causes multiple changes in the histological structure of the liver for both mothers and their offspring, such observations were in accordance with Frieder and Grimm (1984) and Yu et al (1997). Our results indicated that the degree of liver histopathology induced by MSG depends upon the time of exposure.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…MSG was shown to penetrate the placental barrier and to distribute to embryonic tissues (Frieder and Grimm, 1984;Yu et al, 1997). The results of the present work revealed that oral administration of MSG to the pregnant and lactating mother rats causes multiple changes in the histological structure of the liver for both mothers and their offspring, such observations were in accordance with Frieder and Grimm (1984) and Yu et al (1997). Our results indicated that the degree of liver histopathology induced by MSG depends upon the time of exposure.…”
Section: Discussionsupporting
confidence: 76%
“…Many studies have indicated that the application of high doses of MSG to experimental animals may cause lesions of neural structures, the retina, and a series of neuroendocrine disorders, infertility and fatty liver. MSG was shown to penetrate the placental barrier and to distribute to embryonic tissues (Frieder and Grimm, 1984;Yu et al, 1997). The results of the present work revealed that oral administration of MSG to the pregnant and lactating mother rats causes multiple changes in the histological structure of the liver for both mothers and their offspring, such observations were in accordance with Frieder and Grimm (1984) and Yu et al (1997).…”
Section: Discussionsupporting
confidence: 76%
“…Two studies were done in Wistar rats, exposing them to MSG in their drinking water during the last 2 weeks of gestation [18,19]. In the first study [18], MSG was provided as 5 g/100 mL of water resulting in an estimated dose of 10 g/kg.…”
Section: Discussionmentioning
confidence: 99%
“…Frieder and Grimm [113,114] have demonstrated that feeding MSG to pregnant rats can lead to severe alterations in learning that only affected the male rats, again demonstrating a male preponderance of toxic effects. It has also been shown that sensitivity to glutamate increases after birth [115,116].…”
Section: Effect Of Dietary Food Additive Excitotoxinsmentioning
confidence: 99%